Alterações celulares e variações comportamentais de caramujos do gênero Biomphalaria hospedeiros intermediários do Schistosoma mansoni - Coelho, João Rodrigues (2004)
Schistosomiasis is one illnesses that in Brazil still is a serious problem of public health. Ambient, mannering and immunological alterations occured in its intermediate hosts can predict the success or not of one infection. The alterations that occured during the development of an infection involve internal and external factors on the molusc. Among the interns the cellular alterations (hemocytes) and humoral (serum) have been sufficiently studied. In relation to external the temperature was one of the factors chosen for us to evaluate its importance in the relation snail-parasite, mainly because almost the totality of the works approaching this subject dates of the fifty decade. This work had as objective study the resistance and susceptibility of snails of the genus Biomphalaria ahead of the S. Mansoni infection in front of endogenous and exogens factors. Hemocytes of B. glabrata had been gotten according to praised technique and evaluated about its fagocitary capacity, using the technique of reduction of the MTT, being its values quantified for absorbancy 570mm. B. glabrata snailswere also infected in the temperatures of 15oC, 20oC and 30oC and analyzed about the elimination of cercaries to the 30 and 60 days after-infection (DPI). In another experiment, a group of B. tenagophila (CF) - susceptible, received serum from B. tenagophila (Taim) - resistant, being later infected by the S. mansoni and observed about the alteration of the resistance level. Our results show that the behavior of the hemocytes about its fagocitary activity presented significant values between B. glabrata groups not infected in its compared basal state with the not infected and cooled group, as also the same groups when activated by zimozan. Another gotten data shows that the reduction of the temperature influences in the infection development with significant differences (p<0,05) between 15oC and 30oC. We also observe that the serum transference conferred an increase in the number of resistant snails originally susceptible around 50% in comparison to the group not immunized (p<0.05). The extrapolation of these data can take to one better understanding of schistosomiasis on the epidemiologist point of view. The results gotten allow us to conclude that the fagocitary activity of the hemocytes of B. glabrata is influenced by the temperature, as also that the transference of serum of B. tenagophila resistant for B. tenagophila susceptible, increased the resistance of this last one. Finally, we can also affirm that the temperature influences directly in the capacity of infection of B. glabrata by the S. mansoni.